UJI AKTIVITAS ANTIBAKTERI DAUN JERUK KALAMANSI (Citrofortunella microcarpa) TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Deza Oktasila; Nurhamidah Nurhamidah; Dewi Handayani (University of Bengkulu, 2019)
This study aims to examine the antibacterial activity of ethanol extract and essential oil of Kalamansi citrus leaves (Citrofortunella microcarpa) against Staphylococcus aureus and Escherichia coli bacteria. The raw material of Kalamansi citrus leaves is obtained from the Village of Pondok Kubang, Bengkulu Tengah (3.70060S, 102.35780E). Ethanol extract from Kalamansi citrus leaves was obtained by maceration using ethanol 96%, then ethanol extract was made dilution concentration 40 ; 20; , 10; and 5%. The essential oil of Kalamansi citrus leaves is obtained by water-vapor distillation, then made variations of concentration 20;, 15;, 10; and 5%. The method used to test the antibacterial activity is the paper disc diffusion method , the antibacterial activity is shown by the diameter of the inhibiting zone formed. The data of antibacterial test result were analyzed by using One Way Anova test which showed the effect of treatment on the growth of test bacteria seen from the value (P <0,01) and continued by Duncan test to know the effect of the treatment. The results showed that ethanol extract of Kalamansi citrus leaves had antibacterial activity against S. aureus and E. coli bacteria with moderate inhibitory diameter is 7.20 and 5.73 mm at concentration 40%, while antibacterial activity on essential oil of Kalamansi citrus leaves is categorized as strong with inhibition zone diameter is 14.83 and 13.00 mm at concentration 20%.